Khatmul Hadits Riyadhus Shalihin bil Hifzhi di Pondok Pesantren Wali Songo Situbondo - Umi Nuriyatur Rohmah; Hanief Monady; Muhammad Hasan Said Iderus (NALAR, 2023)
In Living Hadith Studies, there are three variants of traditions, there are written tradition, practical tradition, and oral tradition. The research talks about an oral tradition that happens at Wali Songo Islamic Boarding School in Situbondo, it is Khatmul Hadith bil Hifzhi. It is focussing on knowing the practice and interptetation of tradition of Khatmul Hadith. It is description research, which is describes sistematicly the practical of living hadith in Wali Songo Islamic Boarding School by phenomenology approach with social action theory by Max Weber. The research concludes that, firstly, Khatmul Hadith tradition is a practice of reading all of the hadiths in Riyadhus Shalihin by memorizing the hadith (bil hifzhi) and then reading the prays for the closure, and also do some discussionsand questions about all around the interpretations of hadith from the boarding school caretakers. Secondly, the interpretation of the Khatmul Hadith based on Maz Weber’s theory, there are four categories of act, there are the traditional act as a form to conserves traditions of Mecca’s islamic scholars, the afective act to shows the happiness when doing the discussions with the Caretakers and get a good grades, the instrumentally rational act, as a practice of muraja’ah for the students, the values rational act, as for obtaining Allah’s pleasures and the Prophet’s syafa’ah, also obtaining the blessings from the hadith readings.